Multiobjective Transportation Problem Using Fuzzy Decision Variable ThroughMulti-Choice Programming - REDDY, DR.RAJESHWARA; Lakshmi, T. (The journal of contemporary issues in business and government, 2020)
Using fuzzy decision variables, this work examines the examination of the Multi-Objective Transportation Problem (MOTP). When solving a Transportation Problem, the decision variable is usually considered as a real variable. There are a lot of multi-choice fuzzy numbers in this work, but the decision variable in each node is chosen from a collection of those values. Multiobjective Fuzzy Transportation Problems are created when numerous goals are included in a transportation issue with a fuzzy decision variable (MOFTP). We provide a novel mathematical model of MOFTP that incorporates fuzzy goals for each of the objective functions. After that, the multi-choice goal programming methodology is used to define the model’s solution method. For further proof of this article’s value, a numerical example is provided.